2022
DOI: 10.1590/2317-1782/20212021157en
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of different exercises in the vocal space of women with and without vocal nodules

Abstract: Purpose To investigate the immediate effect of voiced tongue vibration (VSL), high-resistance straw in the air (CAR), and overarticulation (OA) on the vocal space of vocally healthy women (MVS) and with vocal nodules (MNV). Methods 12 women participated in the MNV and 12 women in the MVS, allocated to perform the vocal exercises of VSL, CAR, and OA. Each participant performed only one of the three proposed exercises, for 5 minutes, preceded and followed by recording a sequence of vehicle sentences for extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Another study 14 demonstrated that male and female speakers produced vowels with F1 and F2 values relatively close to the targets of native speakers of the state of Paraíba (PB), and the mean values for non-native male speakers were almost identical to the means of native speakers. Formantic measurements are the main acoustic correlates associated with the description of vowel segments 15 . In the present findings, the values of vowel /ɛ/ formants were not sufficient to differentiate pairs of siblings with auditorily similar voices.…”
Section: Discussionmentioning
confidence: 99%
“…Another study 14 demonstrated that male and female speakers produced vowels with F1 and F2 values relatively close to the targets of native speakers of the state of Paraíba (PB), and the mean values for non-native male speakers were almost identical to the means of native speakers. Formantic measurements are the main acoustic correlates associated with the description of vowel segments 15 . In the present findings, the values of vowel /ɛ/ formants were not sufficient to differentiate pairs of siblings with auditorily similar voices.…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo 14 demonstrou que os falantes, masculinos e femininos, produziram vogais com valores de F 1 e F 2 relativamente próximos aos alvos do falante nativo do estado da Paraíba (PB), os valores médios para falantes não nativos do sexo masculino mostraram-se quase idênticos às médias dos falantes nativos. Medidas formânticas são os principais correlatos acústicos associados à descrição de segmentos vocálicos 15 . Nos achados da presente pesquisa, os valores dos formantes da vogal /ɛ/ não foram suficientes para diferenciar pares de irmãos com vozes auditivamente semelhantes.…”
Section: Discussionunclassified